KONSEP REHABILITASI SOSIAL PADA ANAK KONFLIK HUKUM (AKH) - Ahmad Nasrudin Fadli; Wiwik Afifah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Children in conflict with the law must be responsible for the violations/crimes committed, but also have the right to receive rehabilitation including social rehabilitation. This article aims to determine the concept of social rehabilitation for children in conflict with the law. As the Juvenile Criminal Justice System has regulated diversion and the rights of children as suspects. Children in conflict with the law must be held accountable for their actions either through formal legal processes or through diversion. In accountability through formal legal processes and diversion they get social rehabilitation rights, social rehabilitation is a process of re-functionalization and development so that a person is able to carry out his social functions well in social life. Social rehabilitation is an action taken against children who are in conflict with the law through diversion for children. If through the criminal justice process for children over 12 years old, the child will receive a determination of social rehabilitation measures at the Social Welfare Institution (LPKS) within a certain period of time with the supervision of social workers carried out under the Ministry of Law. and Human Rights (Kemenkumham).